The discursive practices that reveal the exercise of motherhood in the prison context: Reflections from the study "Giving birth in the Shadow" - Goularte , Roana Funke; Madruga , Thayane Santos; Alves , Carla Rosane da Silva Tavares; Souza , Antônio Escandiel de (Seven Editora, 2024)
This text addresses a fragment of what is the motherhood of women prisoners and has as its starting point the study carried out by researchers Ana Gabriela Braga and Bruna Angotti. The research was carried out between 2013 and 2014 in Brazilian and Argentine prisons and, with the support of the Institute of Applied Economic Research (Ipea), the results gave rise to the report "Giving birth in the shadow: current conditions and future possibilities for the exercise of motherhood by women in prison", published in 2015 and the book "Giving birth in the shadow: exercise of motherhood in prison", published in 2019. Using the theoretical-methodological assumption of Critical Discourse Analysis, we conducted an analysis of the works cited, with the objective of fostering discussions about the reality of women deprived of liberty in the gestational and puerperium periods and drawing attention to the discrepancy between legislation and practice. DOI:https://doi.org/10.56238/sevened2024.001-046